KINERJA PEGAWAI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KABUPATEN PUNCAK JAYA PROVINSI PAPUA - Wonda, Eri (HOLISTIK, Journal Of Social and Culture, 2013)
The working performance is quite crucial because it contains potential dimensions like efficiency, effectiveness, ability, and motivation of working as well as a good management. In doing a work, an employee ought to have high working performance. However, mostly the employees have a low performance in working. Such low performance will arouse a problem for an organization or institution. This research aims to know the working performance of the employee in Education, Youth, and Sport Department of Puncak Jaya Regency, Papua Province. The result of the research shows that the working performance is not effective enough both qualitatively and quantitatively. This is caused by some factors such as the low motivation of the leader toward his subordinates, the low responsibility and monitoring potency of a leader, the low assertiveness of working discipline, uncomfortable working environment, the lowness of human resources, and the management system which is not good enough. From this research, it can be concluded that the working performance of the employees in Education, Youth, and Sport Department of Puncak Jaya Regency is not quite effective. Keywords : efficiency, effectiveness, ability, motivation